Kontribusi Perusahaan Multinasional terhadap Pengembangan Sektor Ekonomi di Indonesia - Fadilla Syamrotul Puadah; Dea Sopianti; Perwito Perwito (Pusat Riset dan Inovasi Nasional, 2025)
indonesia, the world's 15th largest economy, receives less foreign direct investment than any other developing country, both within and outside its region, with a population of 270 million people and abundant natural resources. According to Indonesia's Central Bureau of Statistics, the country's BPD at that time stood at US1.49 Trillion. Over the past ten years, foreign direct investment into Indonesia has continued to increase. Multinational companies are companies that consist of various other companies that provide foreign investment opportunities and conduct activities that increase the value of the entity. In addition, multinational companies also have an important role in the global economy and are also leaders in various industrial sectors. The purpose of this research is to find out Multinational Companies that have an important role in the Indonesian economy. This research method uses a qualitative method by collecting research data from previous researchers as a reference. The results of the research we found show that the role of multinational companies has both positive and negative impacts. The positive impact for Indonesia is that they give Indonesia the opportunity to develop its economy through foreign exchange, besides that Multinational Companies also develop digitalization technology for the Indonesian economy. In addition to the positive impact, there are also negative impacts of MNCs, namely, dependence on foreign technology and components, limiting the development of domestic industries, limited technology transfer and development of local companies, decreased domestic investment due to the oligopolistic nature of MNCs, the last is environmental degradation and social inequality caused by MNC operations.